PENGARUH KEPEMIMPINAN KEPALA DESA DALAM PENGEMBANGAN WISATA BAHARI TLOCOR DESA KEDUNGPANDAN KECAMATAN JABON KABUPATEN SIDOARJO - Ariskha Damaiyanti; Hendra Sukmana (LPPM Universitas Abdurrab, 2024)
This research aims to analyze and explain the role of the village head's leadership in the development of Tlocor Marine Tourism and to assess the significant impact of the village head's leadership on this development. The methodology used is a descriptive approach with a quantitative approach, which includes descriptions of respondents and research variables in the form of frequency tables and percentages of questionnaire results, as well as data analysis with simple linear regression using SPSS V.23 software. The population in this study included 3,564 respondents, and the research sample consisted of 193 respondents selected based on the Slovin formula. The research results show that the leadership of the village head has a positive influence on the development of Tlocor Marine Tourism, with a significance value of 0.00 < 0.05. The calculated t value of 17.920 exceeds the t table of 1.653, so the research hypothesis is accepted (Ha is accepted and H0 is rejected). In addition, the correlation coefficient (R) of 0.792 describes the level of relationship between the independent variable and the dependent variable. Meanwhile, the coefficient of determination (R Square) is 0.627, which means that the village head's leadership contributed 62.7% to the development of Tlocor Marine Tourism, while 37.3% of his relatives were influenced by other factors not included in this research.